Dental materials: a pocket guide - Bastin, K. G. Kimberly G. (Elsevier, 2015)
Use this quick guide to learn the essentials of dental materials! Dental Materials: A Pocket Guide describes how to recognize, select, and mix the most widely used materials in modern dentistry. A flip-book format covers each dental material in two pages, with the first page showing photos of the material before and after mixing, and the facing page including step-by-step mixing and use instructions. This compact, spiral-bound guide is ideal for on-the-go study or chairside reference. Flip-book style is ideal for quick identification and quizzing, devoting two pages to each dental material - one with photos, and the other featuring its description - so you can choose to view only the image, only the description, or both. Hundreds of high-quality photographs help you recognize, identify, and select dental materials, showing materials in three ways: 1) as they appear within manufacturer packaging, 2) as they appear in their unmixed forms, and 3) as they appear at the completion of mixing. Need-to-know information includes the form in which the dental material is supplied, its composition, the armamentarium for use, and step-by-step directions on how to mix and use the material. Helpful hints or special considerations highlight specific terms, issues, properties, or clinical uses of the materials. Convenient, easy-to-follow organization groups chapters into the main categories of materials including restorative materials, impression materials, dental waxes, bonding agents, whitening agents, and others. Compact, pocket size with spiral binding is ideal for chairside use or on-the-go study. Equipment Commonly Used to Manipulate Materials chapter sets up a foundation of essential knowledge by describing the equipment needed for work in dental materials. Historical Dental Materials chapter covers older materials that may still have a place within many dental offices. Quick-reference appendices make it easier to look up metric conversion tables along with photos of commonly used brand-name products for each type of material.